Chlorophyll meter reading compared with yield of maize in different levels of nitrogen supply - Segatto, Cristiane; Conte, Rodrigo; Lajús, Cristiano Reschke; Luz, Gean Lopes da (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">Reading the chlorophyll content via chlorophyll meter (SPAD) is a tool of precision agriculture that provides to farmer subsidy to check the performance of the crops before the nitrogen fertilization. The use of chlorophyll meter enables quickly and easily on the results, an alternative to detect the nutritional status of the plants. This study aimed to evaluate the relationship of the chlorophyll meter readings with the yield of corn in different levels of nitrogen supply. The experiment was conducted in the city of Coronel Freitas, Santa Catarina State, Brazil, season 2014/2015. The ratings for the different corn hybrids and supply levels were performed according to the following factors: simple hybrids (SH) with the event VT PRO® (DKB 240 and DKB 290); development stages (V3-V4, V6, V7 and V10) and heading stages (R1). Nitrogen supply levels (NSL) (0% (control), 25%, 50%, 75% and 100% of the recommended dose (RD)). The experimental design was a randomized complete block design, arranged in a split plot design with three replications, totaling 30 installments. The variables analyzed responses were: reading SPAD and yield. Data were submitted to analysis of variance by F test and analysis of simple linear correlation with the coefficient of Pearson (rx,y) and regression with the choice of mathematical models by the coefficient of determination (R2). The readings taken by the equipment can replace with good precision, the traditional determinations of chlorophyll content for DKB 240 and 290 hybrids, correlating positively with yield.